Nowa Muzyka i przyjemność w serii utworów audiowizualnych ASMR Neo Hülckera - Pasiecznik, Monika (Res Facta Nova, 2020)
New Music developed in the twentieth century under the influence of Theodor W. Adorno’s philosophy. Its sense, according to the philosopher, lies in social criticism, which the composer accomplishes through radical artistic innovation, and the distance from the audience’s expectations. The sensual pleasure of sound reception is not included in the concept of New Music, which preferably should not appeal to anybody, as it “took on the shoulders darkness of the world and all its guilt, and sees its only happiness in knowing misery” (Adorno). In the ASMR series, the German composer Neo Hülcker breaks this paradigm of perception and proposes a radically different interpretation of New Music. ASMR, or Autonomous Sensory Meridian Response, is a sensation of pleasant tingle, caused by subtle acoustic-haptic phenomena, such as amplified murmurs, whispers, touching objects and materials. Millions of people around the world are watching ASMR videos on YouTube that let them relax nicely. In such video compositions as ASMR Tutorial: How to Play “Pression” by Helmut Lachenmann, ASMR Tutorial: How to Play Mark Andre or ASMR Unwrapping the Piano & iv 11a, and Peter Ablinger: weiss/ weisslich 3 – [super soft ASMR] Neo Hülcker investigates the similarity of sound material of illustrative pieces of New Music and ASMR, raising the question of whether New Music can make someone feel tingly. Presenting in the context of ASMR works by Helmut Lachenmann, Mark Andre and Peter Ablinger, Hülcker explores the hidden potential contained in the most radical aesthetics of New Music, namely the suppressed carnal pleasure. The article is an attempt to show the ways how Neo Hülcker redefines the concept of New Music, entering in it the sensual experience of sound.